2023
DOI: 10.3389/fmicb.2023.1167085
|View full text |Cite
|
Sign up to set email alerts
|

Henipavirus zoonosis: outbreaks, animal hosts and potential new emergence

Abstract: Hendra virus (HeV) and Nipah virus (NiV) are biosafety level 4 zoonotic pathogens causing severe and often fatal neurological and respiratory disease. These agents have been recognized by the World Health Organization as top priority pathogens expected to result in severe future outbreaks. HeV has caused sporadic infections in horses and a small number of human cases in Australia since 1994. The NiV Malaysia genotype (NiV-M) was responsible for the 1998–1999 epizootic outbreak in pigs with spillover to humans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Since 2001, NiV-B showed more extensive circulation [ 27 ], justifying the higher number of genomes in the public databases. Bangladesh reported cases almost annually between 2004 and 2015, a pattern described in previous studies [ 28 , 29 , 30 ], with most outbreaks occurring in winter months.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2001, NiV-B showed more extensive circulation [ 27 ], justifying the higher number of genomes in the public databases. Bangladesh reported cases almost annually between 2004 and 2015, a pattern described in previous studies [ 28 , 29 , 30 ], with most outbreaks occurring in winter months.…”
Section: Discussionmentioning
confidence: 99%
“…This process occurs through the interaction of two glycoproteins on the viral surface: an attachment protein (H, G, or HN, based on the extent of neuraminidase and/or hemagglutinin activities) and a fusion protein (F) [ 21 ]. These viruses employ ephrin-B2 and ephrin-B3 receptors to enter host cells [ 1 ]. This allows them to infect a wide range of tissues, including respiratory epithelium and neural cells.…”
Section: Consider Public Health Implicationsmentioning
confidence: 99%
“…Henipaviruses are a group of viruses that have the capability to be transmitted amongst the bats as well as other animal species and humans through spillover events. The primary viral organisms within this group encompass the Nipah virus (NiV) and Hendra virus (HeV), both of which belong to the genus Henipavirus in the family Paramyxoviridae [ 1 , 2 ]. The family Paramyxoviridae consists of a diverse collection of enveloped RNA viruses with single-stranded negative-sense genome, which infect both animals and humans [ 3 ].…”
mentioning
confidence: 99%
“…The reported outbreaks from 1998 onwards indicated the dominance of the NiV-B clade compared with NiV-M, with the prevalence of the former in humans ( 13 ). This demands a thorough study to elucidate the underlying factors contributing to the observed variations in symptoms and mortality rates among individuals infected with NiV originating from disparate geographical locations.…”
Section: Introductionmentioning
confidence: 99%